Necessary and sufficient conditions for local Pareto optimality on time scales - Malinowska, A.B.
We study a multiobjective variational problem on time scales. For this problem, necessary and sufficient conditions for weak local Pareto optimality are given. We also prove a necessary optimality condition for the isoperimetric problem with multiple constraints on time scales. © 2009 Springer Science+Business Media, Inc.